CONHECIMENTO, UNIVERSIDADE E INOVAÇÃO: COMO SE RELACIONAM NA GERAÇÃO DE INOVAÇÃO BASEADA EM CONHECIMENTO - Kelly Cristina Benetti Tonani Tosta; Fernando José Spanhol; Humberto Tonani Tosta (Revista Gestão Universitária na América Latina, 2016)
Universities as generators and diffuse rs of knowledge are innovation agents when they interact with the environment. The role of the university in support of innovation also depends on the regional context, what means that not all universities need to adopt the same behavior in terms of suppor t to innovation policy. This way it is necessary to study further the relationship between the university and society to promote deeper understanding of each one’s role in this relationship in order to produce innovation. A systematic review of the literat ure and a documental research were carried out with the purpose of knowing better the area and checking if this perception. Thus, this paper aims to deepen this analysis by conducting a systematic review performed based on the seven basic steps proposed by Jackson et al (2004). Based on this discussion, there were raised documents that describe the functioning of the Brazilian National System of Innovation and from the interface between the results of the systematic review and document analysis, it was desi gned the role of the university in this system. There were also identified the catalysts factors of innovation that point to the results of academic research that impact on economic development. It is suggested that this paper be followed by empirical rese arch that can demonstrate practical results of the role of universities in innovation.